2008
DOI: 10.2147/copd.s3483
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of mild chronic obstructive pulmonary disease

Abstract: Chronic obstructive pulmonary disease (COPD) is an epidemic in many parts of the world. Most patients with COPD demonstrate mild disease. The cornerstone of management of mild disease is smoking cessation, which is the only proven intervention to relieve symptoms, modify its natural history and reduce mortality. For asymptomatic patients, it is the only required therapy. Short-acting bronchodilators can be added on an as needed basis for those with intermittent symptoms and regularly for those with persistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…The main limitation to this study is that BSMCs from COPD group were exclusively from subjects with mild COPD because of sample availability. However, it is also known that subjects with mild COPD presented underlying inflammation in the airways and are at increased risk of respiratory infections compared to healthy subjects (37,38). Another limit of the study was that no available data on the vitamin D status or supplements or additional medication for the subjects included in this study, as this information is not available from the supplier.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation to this study is that BSMCs from COPD group were exclusively from subjects with mild COPD because of sample availability. However, it is also known that subjects with mild COPD presented underlying inflammation in the airways and are at increased risk of respiratory infections compared to healthy subjects (37,38). Another limit of the study was that no available data on the vitamin D status or supplements or additional medication for the subjects included in this study, as this information is not available from the supplier.…”
Section: Discussionmentioning
confidence: 99%
“…Although all longitudinal changes found here were small, results indicate that disease progression from early to higher COPD grades implies loss in HRQL. Therefore, efficient interventions that slow disease progression, such as smoking cessation approaches, are not only clinically but also from the perspective of quality of life very reasonable at early stages of disease [ 24 , 25 ]. Our results are in accordance with previous studies which found a negative relationship between HRQL and COPD which increases with disease severity [ 12 , 26 - 30 ].…”
Section: Discussionmentioning
confidence: 99%